A critical appraisal of isokinetic knee flexor-extensor strength profiling in elite soccer players - Eustace, S. (Edge Hill University, 2018)
Epidemiological research has identified thigh musculature and knee ligament injuries are of most concern in professional soccer. With strength identified as a modifiable risk factor, isokinetic dynamometry has become a popular means of injury screening. However, isokinetic assessments are criticised based on their lack of functional relevance to injury aetiology. Study one describes isokinetic screening of the thigh musculature in an elite cohort of male soccer players assessed at 60, 180 and 270º·s-1 across four knee joint angles (70-40°). This study identified strength characteristics were velocity and angle dependent, advocating the use of novel metrics and a range of angular velocities for future isokinetic screening. Study two identified these procedures of assessment were modifiable during late stage rehabilitation of an elite soccer player. When considering the influence of gender and age on lower limb injury incidence, studies three and four identified the proposed isokinetic procedures were sensitive to differences in playing age between male and female youth and adult soccer players. In addition to isokinetic assessments, kinematic analysis of functional movements were completed. Study five comprised kinematic (sagittal and frontal planes) assessment of single leg hop and change of direction tasks performed using sidestep and crossover techniques with female soccer players. When considering previous criticisms of isokinetic testing not being functionally relevant, the knee angles and angular velocities identified in study five were used to predict knee flexor and extensor torque expressed by knee joint angle and velocity (study six). Study seven compared the predicted strength values to the knee joint moments exhibited during the hopping tasks. Strength assessments should use joint angle and velocity to profile musculature strength with increased functional relevance, and may identify additional training needs. These studies also allow strength profiling during the completion of functional tasks that may inform increasingly specific interventions.